Iliac arteriovenous fistula presenting with ascites - Yılmaz, Yunus Keser; Sarıkaya, Savaş; Okur, Aylin; Çelikbilek, Asuman; Atalay, Tugay; Akyol, Lütfi; Sözen Gencer, Nagehan; Çelik, Serkan; Ekim, Hasan (Turkish Journal of Gastroenterology, 2014)
Abstract Arteriovenous fistula presents rarely with ascites. Diagnosis, with an elusive clinical presentation, is often incidental or delayed. A 35-year-old woman presented with ascites and cardiac decompensation. Contrast enhanced computed tomography revealed arteriovenous fistula between the left common iliac artery aneurysm and the left common iliac vein. The patient underwent endovascular treatment with arterial access was performed, with implantation of a stent graft in the iliac artery to cover the fistulous communication. At follow-up 1 month later, she was asymptomatic without ascites. Arteriovenous fistula should be considered in the differential diagnosis of patients with ascites and cardiac decompensation. The endovascular treatment of the arteriovenous fistula should be considered as a first line option.